Electrical remodeling of preoptic GABAergic neurons involves the Kv1.5 subunit. - Iustin V Tabarean (PLoS ONE)
The electrogenic machinery of an excitable cell can adapt in response to changes in input, genetic deficit or in pathological conditions, however the underlying molecular mechanisms are not understood. In cases of genetic deletion it is commonly observed that a channel subunit from the same family replaces the missing one. We have previously reported that Kv4.2-/- preoptic GABAergic neurons display identical firing characteristics to those of wild-type neurons despite having reduced A-type currents, and that, surprisingly, they present a robust upregulation of a delayed rectifier current, the nature of which is unknown. Here, using pharmacology, qPCR and Western blots we report that, although the wild-type neurons express several Kv subunits, the upregulated current is conducted by the Kv1.5 subunit exclusively. Thus, this study reveals the molecular nature of a novel mechanism of electrical remodeling in central neurons.